LIVING IN THE CLOUDS: A NEW HIGH-ELEVATION SPECIES OF VANILLA (ORCHIDACEAE, VANILLOIDEAE) FROM PERÚ - Damian, Alexander; Mitidieri, Nicole (Phytotaxa, 2020)
Vanilla armoriquensis, a new species belonging to subgen. Vanilla, is described and illustrated based on living material from Peru. The new species is similar to V. costaricensis but can be easily distinguished by the larger sepals and petals, and a lip with a well-developed triangular apex, bearing a callus with prominent, broad keels, that has an orange coloration at the base and above the middle.